Effects of Service Quality on Customers Satisfaction on Botswana’s Mobile Telecommunications Industry - Lekobane, Khaufelo Raymond; Selelo, Gorata Bessie (Archives of Business Research, 2017)
Botswana’s telecommunications sector has shown significant growth over the years. This is evidenced by the increase in the number of mobile operators, coupled with a drastic increase in the number of consumers. Notwithstanding this, the mobile sector is challenged to continually find ways to ascertain that their products and services meet customers’ expectations, in order to provide improved quality of service and ensure customer satisfaction. This study therefore, examines the relationship between service quality and customer satisfaction in the mobile sector and compares levels as well as analyse the determinants of service quality. The SERVQUAL model was adopted for this study, through which twelve dimensions of service quality were explored and measured. Principal component analysis was employed to compute the customer satisfaction and service quality indices. The regression results showed that, across all mobile operators; Assurance, Credibility, Security and Tangibles are the major dimensions that are significantly and positively related to customer satisfaction. Therefore, service providers need to focus on issues of assurance, credibility, security and tangibles among others, to increase satisfaction levels among their customers.